2021
DOI: 10.1590/1519-6984.235052
|View full text |Cite
|
Sign up to set email alerts
|

Silicon as an attenuator of drought stress in plants of Oryza sativa L. treated with dietholate

Abstract: Silicon (Si) is an element that can improve the growth and development of rice plants in water-deficient environments because it is an enzymatic stimulant, signaling for production of antioxidant compounds. Therefore, the aim of this study was to examine the relationship between water deficiency and the effect of Si on two rice cultivars whose seeds were treated with dietholate. The experimental design was fully randomized with three replicates, and treatments were organized in a 3x2x2x4 factorial arrangement:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
(49 reference statements)
1
2
0
Order By: Relevance
“…In the present study three different sources of Si were tested but found no signi cant difference among them for accumulation of chlorophyll (except chlorophyll a in T. Aus rice). The results are quite similar with the ndings of Cassola et al (2021), who also found no signi cant difference between the sources of Si for chlorophyll a and b contents. Increasing rates of Si supplementation steadily increases the chlorophyll a and b content both in T. Aus and T. Aman rice.…”
Section: Pearson Correlation Co-e Cientsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study three different sources of Si were tested but found no signi cant difference among them for accumulation of chlorophyll (except chlorophyll a in T. Aus rice). The results are quite similar with the ndings of Cassola et al (2021), who also found no signi cant difference between the sources of Si for chlorophyll a and b contents. Increasing rates of Si supplementation steadily increases the chlorophyll a and b content both in T. Aus and T. Aman rice.…”
Section: Pearson Correlation Co-e Cientsupporting
confidence: 90%
“…But the regression relation was not linear, rather it follows the quadratic model which indicates that in a certain level of Si application grain yield reaches it's maximum then declined. The quadratic relationship of Si application and grain yield of rice was also described byCassola et al (2021) andde Souza et al (2021). From quadratic regression model it was found that the optimum rate of silicic acid, sodium meta silicate and calcium silicate were 32.2, 25.7 and 23.6 kg Si ha -1 for T. Aus rice, and 42.9, 25.8 and 24.5 kg Si ha-1…”
mentioning
confidence: 72%
“…In the plant, Si provides higher structural rigidity of the tissue, favors osmotic adjustment (Yin et al, 2013;Lima et al, 2019), and increases photosynthetic and water use efficiency (Cooke and Leishman, 2016;Thorne et al, 2020;Cassol et al, 2021), regulating physiological processes. The beneficial effect of Si is associated with the fact that this element promotes an increase in photosynthetic pigments and gene and phytohormone expressions, in addition to the activity of antioxidant enzymes and amino acids capable of relieving or delaying oxidative stress (Chen et al, 2011;Parveen et al, 2019).…”
Section: Evaluated Morphophysiological Characteristicsmentioning
confidence: 99%